Conventionality control by the administrative function: favorable arguments (Euro-Latin American Journal of Administrative Law, 2024)
The jurisprudence of the Inter-American Court of Human Rights states that all State bodies, within the framework of their competences, must carry out conventionality control. International jurisprudence indicates that all state functions exercised by the Powers of the Republic, as well as bodies not classically identified within any of those Powers, must carry out ex officio control of the conventionality of legal norms and state practices. However, in Brazil this practice does not occur among bodies that perform administrative functions, with a gap between international jurisprudence and the behavior of national public agents in the exercise of their powers. The article presents the main arguments in favor of exercising the technique through administrative functions, positioning itself in the extensive current regarding the subject competent to carry it out.